Resilience and Rural Poverty Reduction - A Path to Reinvented Nation: A Case Study Approach (Trinity Journal of Management, IT & Media (TJMITM), 2022)
Rural India plays an important role in the socio-economic development with the help of farmers, daily wage workers, small and marginal producers, agricultural labourers etc. Having understood the enormity of rural people’s aspirations, it is important to reshape the roles and functions based on the rural areas. Strengthening rural women’s sustainable livelihood and wellbeing can help them to be resilient in facing challenges and difficulties. The development indicators have to change for the upliftment of the women. Aspects like community help in terms of knowledge and capacity-building along with external support from governments and rural welfare markets can bring a drastic transformation in the upliftment of these rural women. The aim of this study is to highlight activities that build resilience and reduce poverty by protecting and promoting livelihoods, particularly agriculture-based livelihoods, given that they are the backbone of India’s rural economy. The study highlights cases of few rural women from Sakri Khas village, Baijnath Tehsil, Himachal Pradesh, India where implementation of rural women’s livelihood activities has helped in the socio-economic empowerment of these women.
Keywords: Rural women; Economic status; Growth and Development; Livelihood